B15 Rat bone marrow derived mesenchymal stem cells post differentiation to neurotrophic factor secreting cells migrate towards quinolinic acid lesion. (16th November 2010) - Sadan, O; Shemesh, N; Cohen, Y; Melamed, E; Offen, D
Abstract : Background: Quinolinic acid (QA) induced striatal lesion is a well established model for excitotoxicity, one of the key hallmarks of Huntington's disease pathophysiological processes. Stem cell based treatment is a promising frontier for this incurable condition. One of the major caveats of stem cell transplantation is their fate post transplantation. Aims: To follow the transplanted cells' fate using in vivo MRI scans followed by histological study. Methods: Rat mesenchymal stem cells (MSC) went through a two phase medium based differentiation protocol containing N2, growth factors, IBMX and cyclic AMP. The protocol's output was assessed using immunocytochemistry and immunoblotting analysis of the medium post differentiation. Rats were treated with 250 nmol QA injected into the left striatum. 250 000 differentiated cells, prelabelled with PKH-26 fluorescent dye and SPIO, were transplanted 5.2 mm posterior to the lesion. The control group was injected with SPIO. Rats underwent serial MRI scans to detect cell migration in vivo. On the 19th day animals were sacrificed and brains were removed for immunostaining. Results: Rat MSC post differentiation exhibit a mixed neuronal and astrocyte identity. The cells produce and secrete NGF, BDNF and VEGF. MRI 100×100×75 (μm) 3 3D GE images revealed that cells migrate along a distinct route towards the lesion and accumulate over time close to hyperintense regions where damage is probably more severe. Histological study discovered a similar distribution of the cells and phagocytosis only partially occurred. Conclusions: The outcomes show that the differentiated neurotrophic factor secreting cells react and migrate towards a QA lesion, and therefore survive 19 days post implantation. MRI in vivo scans are a reliable method for monitoring the cells, and the results correlate with the histological appearance. This gives hope for using these cells as treatment of neurodegenerative diseases.